CNC double spiral tool-path generation based on parametric surface mapping. (October 2015) - Zhou, Bo; Zhao, Jibin; Li, Lun
Abstract: High-speed machining (HSM) has been an important method for machining complex parametric surface. Tool-path planning for HSM has a significant impact on processing efficiency and surface quality. A new double spiral tool-path generation algorithm for HSM is proposed in this paper. First, the isothermal lines which satisfy the machining parameters in the mapping parametric domain are computed by means of constructing a thermal conductivity model and solving partial differential equations (PEDs). Furthermore, a smoothness optimization method is proposed to improve the smoothness of the isothermal lines and avoid taking up too much memory. Then, the mapping rules are constructed and the trajectory is planned out in the standard parametric domain in order to generate double spiral trajectory in the corresponding parametric domain. Finally, the trajectory is mapped onto the parametric surface to obtain the tool-paths, and the tool-paths linking method is planned for complex multi-domains. This method can realize the precision milling of complicated parametric surface without tool retractions, and meanwhile it improves the uniformity of the tool-paths and machining efficiency. Our method has been experimented in several simulations and validated successfully through the actual machining of a complicated pocket. The results indicate that this method is superior to other existing machining methods, and it can realize HSM of complicate-shaped pocket based on parametric surface. Highlights: We study a new double spiral tool-path generation algorithm for 5-axis HSM. We call a smoothness optimization method during solving PDEs to smooth curves. Machining parameters (e.g., path interval and step length) can be guaranteed. Mapping rules are based on the same ranges of NURBS curve and parametric domain. Our tool-paths have a self-complementary structure and can be suitably linked.